A descriptive analysis of Ilongo suffixes - Sobrepena, Lucila P. 1925-
This is a descriptive analysis of Ilongo suffixes. Suffixes in Ilongo are bound forms which may be added to a root or a stem to form a new class of words. They may be derivational or inflectional in nature.